Consensus Guidelines from the American Society of Pain and Neuroscience for the Use of 60-Day Peripheral Nerve Stimulation Therapy. A NEURON Living Guideline Project - Gill B; Tidwell C; Hagedorn JM; Moreira AM; Lawandy M; Boyett B; Schappell J; Latif U; Pritzlaff S; Skaribas I; Kalia H; Sheth S; et al. (Journal of Pain Research)
Benjamin Gill,1 Cody Tidwell,2 Jonathan M Hagedorn,3 Alexandra M Moreira,4 Marco Lawandy,5 Benjamin Boyett,6 Justin Schappell,7 Usman Latif,8 Scott Pritzlaff,9 Ioannis Skaribas,10 Hemant Kalia,11 Samir Sheth,12 Maricela Schnur,13 Sean Li,14 Denise Lester,15,16 Trevor Ellico,17 Ramana Naidu,18 David Russo,19 Christopher Massey,20 Einar Ottestad,21 Kevin Vorenkamp,22 Henry Vucetic,23 Matthew J Pingree,3 David Abejón,24 Mehul J Desai,25 David Dickerson,26,27 Amitabh Gulati,28 Dawood Sayed,8 Timothy R Deer29 1Omaha Pain Physicians, Omaha, NE, USA; 2Department of Anesthesiology and Pain Medicine, University of Minnesota, Minneapolis, MN, USA; 3Department of Anesthesiology and Perioperative Medicine, Division of Pain Medicine, Mayo Clinic, Rochester, MN, USA; 4Department of Anesthesiology and Pain Medicine, Rush University, Chicago, IL, USA; 5Department of Physical Medicine and Rehabilitation, Montefiore Medical Center, Bronx, NY, USA; 6Department of Physical Medicine and Rehabilitation, University of Missouri, Columbia, MO, USA; 7Department of Pain Medicine, Mayo Clinic Health System, Eau Claire, WI, USA; 8Department of Anesthesiology and Pain Medicine, The University of Kansas Health System, Kansas City, KS, USA; 9Department of Anesthesiology and Pain Medicine, University of California–Davis, Sacramento, CA, USA; 10Expert Pain, Houston, TX, USA; 11Center for Research & Innovation in Spine & Pain, Rochester, NY, USA; 12Sutter Health Systems, Roseville, CA, USA; 13Department of Pain Medicine, Guthrie Clinic, Ithaca, NY, USA; 14National Spine and Pain Centers, Shrewsbury, NJ, USA; 15Department of Physical Medicine and Rehabilitation, Virginia Commonwealth University, Richmond, VA, USA; 16Department of Physical Medicine and Rehabilitation, Richmond VA Medical Center, Richmond, VA, USA; 17Department of Anesthesiology, University of Utah, Salt Lake City, UT, USA; 18MarinHealth Spine Institute, UCSF Affiliate, Larkspur, CA, USA; 19Columbia Pain Management, Hood River, OR, USA; 20Pain Specialists of America, Austin, TX, USA; 21Department of Anesthesiology, Perioperative and Pain Medicine, Stanford University School of Medicine, Stanford, CA, USA; 22Duke University Department of Anesthesiology, Durham, NC, USA; 23University Hospitals Department of Anesthesiology and Perioperative Medicine, Cleveland, OH, USA; 24Unidad de Dolor, Hospital Universitario Quironsalud Madrid, Madrid, Spain; 25International Spine, Pain & Performance Center, Washington, DC, USA; 26Department of Anesthesiology, Critical Care & Pain Medicine, Endeavor Health, Evanston, IL, USA; 27Department of Anesthesia & Critical Care, University of Chicago Pritzker School of Medicine, Chicago, IL, USA; 28Department of Anesthesiology, Memorial Sloan Kettering Cancer Center, New York, NY, USA; 29The Spine and Nerve Center of the Virginias, Charleston, WV, USACorrespondence: Benjamin Gill, Email DrBenjaminGill@gmail.comAbstract: Peripheral nerve stimulation (PNS) has evolved with various applications and durations of therapy. In recent years, extensive data has been developed on a 60-day treatment using a novel approach. Confusion exists on the use of a trial therapy, a permanent implant, and a 60-day duration treatment. The American Society of Pain and Neuroscience (ASPN) seeks to clarify the literature associated with this neuromodulation approach. A diverse group of experts was nominated to provide opinions and guidance based on evidence-graded assessment and clinical knowledge. This guidance is the first to specifically assess the clinical use of 60-day PNS and best medical practice.Keywords: peripheral nerve stimulation, pain medicine, best practices, clinical guidelines